Association of childhood smoking and adult mortality: Prospective study of 120 000 Cuban adults - Thomson, B; Rojas, NA; Lacey, B; Burrett, J; Emberson, J; Peto, R; Lewington, S (Elsevier, 2020)
Background: The average age at which people start smoking has been decreasing in many countries, but insufficient evidence exists on the adult hazards of having started smoking in childhood and, especially, in early childhood. We aimed to investigate the association between smoking habits (focusing on the age when smokers started) and cause-specific premature mortality in a cohort of adults in Cuba.